Novel recombinant protein flagellin A N/C attenuates experimental autoimmune encephalomyelitis by suppressing the ROS/NF-κB/NLRP3 signaling pathway - Li, Li; Deng, Shihua; Liu, Mingquan; Yang, Min; Li, Jin; Liu, Teng; Zhang, Ting; Zhao, Yangyang; He, Miao; Wu, Dongming; Xu, Ying (Frontiers in Pharmacology, 2022)
Multiple sclerosis (MS) is a chronic inflammatory autoimmune disease characterized by demyelination and neurodegeneration, for which traditional treatment offers limited relief. Microglial/macrophage modulation plays a critical role in the pathogenesis of MS. Oxygen free radical accumulation can induce axonal and nerve cell damage, and further promote MS development. We created a new recombinant protein based on flagellin from Legionella pneumophila named flagellin A with linked C- and N-terminal ends (FLaAN/C), which is an independent intellectual property of our team. We previously showed that FLaAN/C might mitigate radiation-induced damage by inhibiting inflammatory responses and oxidative stress. However, whether FLaAN/C protects against MS remains unknown. Here, we investigated the anti-inflammatory effects of FLaAN/C on mice with experimental autoimmune encephalomyelitis (EAE) induced by oligodendrocyte glycoprotein peptide 35–55 (MOG35-55). The mice were injected intraperitoneally with FLaAN/C after the onset of clinical symptoms, then clinical behavior scores and changes in body weight were recorded daily. The spinal lumbar spine in model mice was enlarged and accompanied by inflammatory cell infiltration and demyelination that were reversed by FLaAN/C. FLaAN/C also induced microglia/macrophages to generate less pro-inflammatory (CD86, iNOS, and TNF-α), and more anti-inflammatory (CD206, IL-10, and Arginase-1) cytokines. These findings suggesting that FLaAN/C promoted microglial/macrophages polarization from the inflammatory M1 to the anti-inflammatory M2 phenotype. Moreover, FLaAN/C inhibited release of the inflammatory cytokines, TNF-α, IL-8, IL-6, IL-17, and IFN-γ. These results indicated that the anti-inflammatory effect of FLaAN/C was associated with the inhibited generation of reactive oxygen species. FLaAN/C downregulated the expression of phosphorylated NF-κB-p65 and prevented downstream NLRP3 inflammasome-mediated pyroptosis. Collectively, these results indicated that FLaAN/C prevents pyroptosis by inhibiting the ROS/NF-κB/NLRP3 signaling pathway, and promotes the microglial/macrophage M1/M2 polarization that significantly alleviated inflammation in mouse models of EAE. Our findings suggested that FLaAN/C could be a promising candidate for MS therapy.